The Equilibrium Real Exchange Rate of the Malagasy Franc : Estimation and Assessment - Cady, John (IMF Working Papers; Working Paper ;, 2003)
Employing cointegration techniques, the long-run determinants of Madagascar's real exchange rate are examined from a stock-flow perspective. The long-run behavior of the real effective exchange rate is explained by the net foreign asset position and factors affecting trade flows. An index of the long-run equilibrium real exchange rate is developed to assess the degree of misalignment. The general conclusions are that the Malagasy franc has experienced significant misalignment in the past, but that the recent appreciation of the real effective exchange rate is consistent with changes in the fundamentals, particularly anticipated improvements in the net foreign assets position stemming from Madagascar's eligibility for assistance under the enhanced HIPC Initiative.